Development of ROV Trencher URI-T and its Sea Trial - Hyungjoo Kang; Mun-Jik Lee; Gun Rae Cho; Geonhui Ki; Min-Gyu Kim; Ji-Hong Li (한국해양공학회지, 2019)
An ROV trencher is a type of heavy-duty work class ROV equipped with high-pressure water jet tools for cutting into the sea floor and burying cables. This kind of trencher is mostly used for PLIB operations. This paper introduces the development of this kind of ROV trencher, which has a 698 kW power system, with a 250 kW hydraulic system and two 224 kW water jet systems. The project was launched in January 2014. After four years of design, manufacturing, and system integration, we carried out two sea trials near the Yeongilman port (about 20–30 m in depth) in Pohang to evaluate the system performance in November 2017 and August 2018. Through tests, we found that most of specifications were satisfied, including a maximum bury depth of 3 m, maximum bury speed of 2 km/h, and maximum forward speed of 1.54 m/s.